Project “Positive Attitude”: Promoting school success through social and emotional abilities development. Design for elementary and middle school students, in Portugal - Couceiro Figueira, Ana Paubla (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2012)
This article aims to analyze and explore the development of the Project “Positive Attitude” during the first three years of functioning. This project’s main objective is the promotion of social skills, self-esteem and the social and emotional self-concept of elementary and middle school students. For doing so, the project involves all the school community.